2020
DOI: 10.1186/s12864-020-07005-y
|View full text |Cite
|
Sign up to set email alerts
|

Integrated metabolomics and transcriptomics study of traditional herb Astragalus membranaceus Bge. var. mongolicus (Bge.) Hsiao reveals global metabolic profile and novel phytochemical ingredients

Abstract: Background Astragalus membranaceus Bge. var. mongolicus (Bge.) Hsiao is one of the most common herbs widely used in South and East Asia, to enhance people’s health and reinforce vital energy. Despite its prevalence, however, the knowledge about phytochemical compositions and metabolite biosynthesis in Astragalus membranaceus Bge. var. mongolicus (Bge.) Hsiao is very limited. Results An integrated metabolomics and transcriptomics analysis using stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“…The metabolites with VIP > 1, P < 0.05 and fold change > 2 or < 0.5 were considered statistically significant. To explain the physical and chemical properties and biological functions of metabolites, the online METLIN, 1 Human Metabolome, 2 KEGG databases (using MetaboAnalyst) 3 and metabolomic data (Wu et al, 2020) of A. membranaceus var. mongolicus (published data annotated by MassBank and Bio-PubChem) were used for identification and annotation.…”
Section: Metabolism Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The metabolites with VIP > 1, P < 0.05 and fold change > 2 or < 0.5 were considered statistically significant. To explain the physical and chemical properties and biological functions of metabolites, the online METLIN, 1 Human Metabolome, 2 KEGG databases (using MetaboAnalyst) 3 and metabolomic data (Wu et al, 2020) of A. membranaceus var. mongolicus (published data annotated by MassBank and Bio-PubChem) were used for identification and annotation.…”
Section: Metabolism Analysismentioning
confidence: 99%
“…In metabolomic studies (Li et al, 2019;Wu et al, 2020), a large number of pythometabolites were identified in AMM herbs. In our study, we also found an abundance of phytometabolites from P. ostreatus var.…”
Section: Overview Of Metabolomicsmentioning
confidence: 99%
“…Phenolics, including flavonoids, have been judged as the marker for quality evaluation and standardization of A. membranaceus and its processed products [ 7 ]. Methoxylated flavonoids and their glycosides, such as calycosin and calycosin-7- O - β -D-glucoside, were the major bioactive constituents of A. membranaceus due to their superior bioactivities [ 8 , 9 ]. After glycosylation and methylation, the reactivity and solubility of the flavonoids usually improved and thereby so did their absorption and bioactivity [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the peakonly algorithm, the convolutional neural network-based deep learning method is used to detect true positive peaks in the raw data ( Melnikov et al., 2020 ). Except for these useful methods, a hierarchical five-step filtering approach ( Duan et al., 2016 ) is considered as one of the most efficient methods ( Ju et al., 2019 ), and has been used in some recently published works ( Wu et al., 2018 , 2020 ; Li et al., 2019 ).…”
Section: Reducing False-positive Signals In Lc-ms Analysis Of Plant Metabolomesmentioning
confidence: 99%